KESELARASAN MIKROKOSMOS-MAKROKOSMOS SEBAGAI DASAR PEMBANGUNAN MASA HINDU-BUDDHA DI INDONESIA - Baskoro Daru Tjahjono (Balai Arkeologi Yogyakarta, 2008)
The culture that emerged in Hindu-Buddha period in ancient Indonesia was always related to religious concepts. Therefore, anything being produced at that time should reflect the harmony between micro and macrocosms, or in other words, between human and deities worlds. This could be exemplified by temples and royal palaces from that period. Temples symbolized Mahameru, the mountain regarded as the center of universe; whilst royal palaces as microcosm should have elements and arrangements in favour with the afore mentioned macrocosm.